Excise taxes on sugar-sweetened beverages in Latin America and the Caribbean - Rosa Carolina Sandoval; Maxime Roche; Itziar Belausteguigoitia; Miriam Alvarado; Luis Galicia; Fabio S. Gomes; Guillermo Paraje (Pan American Health Organization, 2021)
Objective. To characterize the design of excise taxes on sugar-sweetened beverages (SSBs) in Latin America and the Caribbean and assess opportunities to increase their impact on SSB consumption and health. Methods. A comprehensive search and review of the legislation in effect as of March 2019, collected through existing Pan American Health Organization and World Health Organization monitoring tools, secondary sources, and surveying ministries of finance. The analysis focused on the type of products taxed, and the structure and base of these excise taxes. Results. Out of the 33 countries analyzed, 21 apply excise taxes on SSBs. Seven countries also apply excise taxes on bottled water and at least four include sugar-sweetened milk drinks. Ten of these excise taxes are ad valorem with some tax bases set early in the value chain, seven are amount-specific, and four have either a combined or mixed structure. Three countries apply excise taxes based on sugar concentration. Conclusions. While the number of countries applying excise taxes on SSBs is promising, there is great heterogeneity in design in terms of structure, tax base, and products taxed. Existing excise taxes could be further leveraged to improve their impact on SSB consumption and health by including all categories of SSBs, excluding bottled water, and relying more on amount-specific taxes regularly adjusted for inflation and possibly based on sugar concentration. All countries would benefit from additional guidance. Future research should aim to address this gap.